2014
DOI: 10.1016/j.earlhumdev.2013.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal maternal depression is associated with low birth weight through shorter gestational age in term infants in Korea

Abstract: Background Maternal prenatal depression is associated with lower offspring birth weight, yet the impact of gestational age on this association remains inadequately understood. Aims We aimed to investigate the effect of prenatal depression on low birth weight, gestational age, and weight for gestational age at term. Study design Prospective cohort study. Subject Data were collected from 691 women in their third trimester of pregnancy who went on to give birth to a singleton at term without perinatal compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
35
2
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 58 publications
1
35
2
1
Order By: Relevance
“…The presence of symptoms suggesting a diagnosis of probable depressive disorder was verified in 14.4% of the pregnant women evaluated; although this finding is lower than that of other countries, ranging from 22.0% to 34.9%, 17,19 our results are similar to the national studies performed with low socioeconomic pregnant women in the second and third trimesters of pregnancy 6,24 . The association between depression and obstetric outcomes is still poorly understood.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…The presence of symptoms suggesting a diagnosis of probable depressive disorder was verified in 14.4% of the pregnant women evaluated; although this finding is lower than that of other countries, ranging from 22.0% to 34.9%, 17,19 our results are similar to the national studies performed with low socioeconomic pregnant women in the second and third trimesters of pregnancy 6,24 . The association between depression and obstetric outcomes is still poorly understood.…”
Section: Discussionsupporting
confidence: 76%
“…The high frequency of MD during pregnancy is supported by the literature in national studies with populations of low socioeconomic status 2,5 and attended by PHC 14 . In international research, the prevalence of psychiatric symptoms, particularly anxiety and depression, varies from 11.8% to 34.9% [15][16][17][18][19] , depending not only on the socioeconomic aspects of the period of time investigated, but also on the tool used in the detection.…”
Section: Discussionmentioning
confidence: 99%
“…The probability of using different psycho-active substances by the mother is increased and has a potential effect on the fetus (3,5–10). In addition, decreased head circumference, low birth weight and decreased reflex response are common effects on the fetus (1114). Contrary to this, a study from Pakistan concluded that antenatal depression is not associated with low birth weight (15).…”
Section: Introductionmentioning
confidence: 99%
“…However, birth weight was not examined independently of gestational age in those studies. Others have found that the association between maternal depression and low birth weight is attenuated when adjusted for gestational age (Chang et al., 2014). A recent meta-analysis of antenatal depression and birth outcomes finds depressed pregnant women are at increased risk for both preterm birth and delivering low birth weight newborns (Grote, et al, 2010).…”
mentioning
confidence: 99%